When to adopt cloud native infrastructure - Garrison, Justin; Nova, Kris (O'Reilly Media, Inc., 2018)
Many companies are building applications for cloud platforms to gain greater agility, cost savings, security, and reliability than they could with similar capabilities in-house. But even the best cloud native application can go to waste without the right design and practices to manage infrastructure. This article provides guidelines to help your company determine when-and if-to adopt your own cloud native infrastructure. You'll learn the impact that building and maintaining infrastructure of this type can have on your applications, people, systems, and business as a whole.
Includes bibliographical references
Keywords: Cloud computing; Infonuagique; Computer architecture